2004
DOI: 10.21000/jasmr04010576
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Impacts of Mountain Top Removal/Valley Fill Coal Mining on Stream Fish Populations

Abstract: Abstract. Little information exists regarding the effects of mountain top removal/valley fill coal mining on stream fish populations in West Virginia and Kentucky. To address this knowledge gap, we conducted a study in cooperation with U.S. Environmental Protection Agency (USEPA) Region III to characterize the fish communities that exist in these regions and to evaluate the effects of these mining operations on fish populations. During 1999-2000, fish assemblages were sampled in 58 sites in West Virginia and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Our fish metrics displayed similar responses to mining as others in the literature (Letterman and Mitsch, 1978;Howells et al, 1983;Ferreri et al, 2004;Schorr and Backer, 2006;US EPA, 2011), but we demonstrated that mine influences are more pronounced at larger spatial scales than previously tested. In the conterminous United States (US), every state has mining within its borders.…”
Section: Importance Of Scalesupporting
confidence: 83%
See 1 more Smart Citation
“…Our fish metrics displayed similar responses to mining as others in the literature (Letterman and Mitsch, 1978;Howells et al, 1983;Ferreri et al, 2004;Schorr and Backer, 2006;US EPA, 2011), but we demonstrated that mine influences are more pronounced at larger spatial scales than previously tested. In the conterminous United States (US), every state has mining within its borders.…”
Section: Importance Of Scalesupporting
confidence: 83%
“…Reduced fish and macroinvertebrate survival and production have been found in streams receiving mine drainage (Letterman and Mitsch, 1978;Howells et al, 1983). The accumulation of both influences from anthropogenic land use plus the unique effects from mines reduces fish species richness and abundance (Letterman and Mitsch, 1978;Howells et al, 1983;Ferreri et al, 2004;Schorr and Backer, 2006;US EPA, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, macroinvertebrate richness in MTR/VF streams is significantly reduced compared to reference locations (Pond, 2010(Pond, , 2012, and freshwater mussel diversity decreases as extent of surface mines increase within catchments of central Appalachian rivers (Warren and Haag, 2005). Additionally, fish species richness is reduced by 50% at sites downstream from MTR/VF (Ferreri et al, 2004). Amphibians, specifically salamanders, are important components of low-order stream ecosystems (Davic and Welsh, 2004); up to 9 species occur within central Appalachian streams (Petranka, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Since freshwater organisms need to keep an osmotic balance with the river water, they are very sensitive to changes in salinity (Williams, 2001;James et al, 2003). When the river salinity increases the most sensitive species, those who are unable to cope with high salinity increases, tend to disappear (Busse et al, 1999;Ferreri et al, 2004;Horrigan et al, 2005;Kefford et al, 2006) having an important impact on the ecosystem functioning (Fritz et al, 2010;Schäfer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%